Binding selectivity-dependent molecular mechanism of inhibitors towards CDK2 and CDK6 investigated by multiple short molecular dynamics and free energy landscapes - Lifei Wang; Dan Lu; Yan Wang; Xiaoyan Xu; Peihua Zhong; Zhiyong Yang (Journal of Enzyme Inhibition and Medicinal Chemistry, 2023)
Understanding selectivity-dependent molecular mechanism of inhibitors towards CDK2 over CDK6 is prominent for improving drug design towards the CDK family. Multiple short molecular dynamics (MD) simulations combined with MM-GBSA approach are adopted to investigate molecular mechanism on binding selectivity of inhibitors X64, X3A, and 4 AU to CDK2 and CDK6. The RMSF analysis and calculations of molecular surface areas indicate that local structural and global flexibility of CDK6 are stronger than that of CDK2. Based on dynamics cross-correlation maps (DCCMs), motion modes of CDK2 and CDK6 produce difference due to associations of X64, X3A, and 4 AU. The calculated binding free energies (BFEs) demonstrate that the compensation between binding enthalpy and entropy of X64, X34, and 4 AU is a key force driving selectivity of inhibitors towards CDK2 over CDK6. This work provides valuable information for designing highly selective inhibitors towards CDK2 and CDK6 and further promotes identification of efficient anticancer drugs in the future.